Bagong Buwan - Diaz-Abaya, Marilou (Regal Home Video.)
Ahmad (Cesar Montano) is a Muslim who lives in Manila as a doctor. His wife Fatima (Amy Austria) and only son Ibrahim (Brian Homecillo) live in Mindanao with Ahmad's mother, Farida (Caridad Sanchez). Ahmad is devastated when he is told that Ibrahim has been killed by a stray bullet fired by vigilantes. Returning to Mindanao, Ahmad finds himself opposing his family wish to stay in their war-torn homeland. In spite of his son's death, Ahmad still wants to live a peaceful life and insists that the best solution for his family is to Manila with him, Musa (Noni Buencamino), Ahmad's brother, disagrees. Musa believes that a war against "the unbelieves" is the only solution and even trains his young son Rashid (Carlo Aquino) for a Muslim warrior's life. An explosion near a public marketplace thrusts Ahmad and his loved ones into the center of a blood conflict between Christians and Muslims, the government and the Moros. Prepared to make the ultimate sacrifice, Ahmad, in his new role as leader, discovers that nobody ever wins a war, and that a culture of peace is better than a culture of war